101 Avoiding Burnout of the Care Home Workforce During the COVID-19 Pandemic and Beyond: Sharing National Learning and Local Initiatives. (16th March 2021) - Johnston, L; Malcolm, C; Rambabu, L; Hockley, J; Shenkin, S D
Abstract: Introduction: COVID-19 in care homes has heightened the risk of staff burnout, undermining already problematic staff retention and low morale. There has been an associated proliferation of resources and online initiatives to support frontline workers, however, few of these are directly targeted at the care home workforce. Care home workers are highly skilled in caring for people with complex needs, but have very variable levels of formal training, and just over half of care homes in Scotland include registered nurses. This project will rapidly collate existing resources and identify, direct from care home workers, their best practice, initiatives, and resources used to support resilience and retention during this pandemic and moving forward. Methods: 1) Rapid review of care home specific evidence and resources (including published research and social media); 2) Online survey of Enabling Research in Care Homes (ENRICH) members across Scotland (n = 55); 3) Case studies within six care homes to identify what is working well and what is not in terms of promoting resilience and emotional support. Results: The rapid review has identified a wide range of resources directed at supporting staff working in care homes; the survey and case studies will provide data on the key learning and resources that have supported staff, and outline the challenges identified. There are many resources available but staff do not access these. The role of the care home manager is key. Key conclusions: This comprehensive review of resources and initiatives will make a valuable contribution to policy and practice designed to reduce burnout and foster retention not just in care homes but more widely across health and social care.